(Pro)renin receptor involves in myocardial fibrosis and oxidative stress in diabetic cardiomyopathy via the PRR–YAP pathway - Shiran Yu (Nature Portfolio, 2021)
Abstract (Pro)renin receptor (PRR) and Yes-associated protein (YAP) play an important role in cardiovascular diseases. However, the role of PRR–YAP pathway in the pathogenesis of DCM is also not clear. We hypothesized that PRR–YAP pathway may promote pathological injuries in DCM by triggering redox. Wistar rats and neonatal rat cardiac fibroblasts were respectively used in vivo and in vitro studies. In order to observe the effects of PRR mediated YAP pathway on the pathogenesis of DCM, animal experiments were divided into 3 parts, including the evaluation the effects of PRR overexpression, PRR RNAi silencing and YAP RNAi silencing. Recombinant-adenoviruses-carried-PRR-gene (Ad-PRR), Ad-PRR-shRNA and lentivirus-carried-YAP-shRNA were constructed and the effects of PRR mediated YAP on the pathogenesis of DCM were evaluated. YAP specific inhibitor Verteporfin was also administrated in cardiac fibroblasts to explore the impact of PRR–YAP pathway on oxidative stress and myocardial fibrosis. The results displayed that PRR overexpression could enhance YAP expression but PRR RNAi silencing down-regulated its expression. Moreover, PRR overexpression could exacerbate oxidative stress and myocardial fibrosis in DCM, and these pathological changes could be rescued by YAP blockade. We concluded that PRR–YAP pathway plays a key role in the pathogenesis of DCM.